2014
DOI: 10.1016/j.breast.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trastuzumab treatment beyond disease progression for advanced/metastatic breast cancer on survival – Results from a prospective, observational study in Germany

Abstract: The hitherto limited evidence for TBP benefit from randomized studies was confirmed. While a number of strong disease-related predictors for survival after first progression could be identified, the positive effect of trastuzumab continuation retained statistical significance in a multivariate model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…Compared with the results from a prospective large observational study and a randomized phase III study involving metastatic breast cancer, which showed that the continued therapy with TBP improves the survival outcome of patients with metastatic HER2-positive breast cancer (19,20), the results of the present study did not demonstrate a clear survival time benefit associated with trastuzumab therapy following first disease progression. However, the magnitude of unadjusted HR (0.63) for PFS in the present study was of the same order as that (0.69) in a German phase III trial comparing trastuzumab plus capecitabine vs. capecitabine alone in HER2-positive breast cancer patients whose disease had progressed during trastuzumab therapy (20), a finding which justified further investigation of HER2-positive AGC.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Compared with the results from a prospective large observational study and a randomized phase III study involving metastatic breast cancer, which showed that the continued therapy with TBP improves the survival outcome of patients with metastatic HER2-positive breast cancer (19,20), the results of the present study did not demonstrate a clear survival time benefit associated with trastuzumab therapy following first disease progression. However, the magnitude of unadjusted HR (0.63) for PFS in the present study was of the same order as that (0.69) in a German phase III trial comparing trastuzumab plus capecitabine vs. capecitabine alone in HER2-positive breast cancer patients whose disease had progressed during trastuzumab therapy (20), a finding which justified further investigation of HER2-positive AGC.…”
Section: Discussioncontrasting
confidence: 98%
“…Preliminary evidence from a small phase II study demonstrated that a trastuzumab plus docetaxel-containing regimen was well tolerated and effective for HER2-positive AGC previously treated with fluorouracil-based chemotherapy; however, in this study, the patients had received no previous therapy with trastuzumab (18). On the other hand, several studies have reported that continued therapy with trastuzumab beyond progression (TBP) improves the survival outcome of patients with metastatic HER2-positive breast cancer (19,20), and represents a practical therapeutic option. However, there is currently no clinical data regarding the efficacy of trastuzumab for HER2-positive AGC progressing during trastuzumab-based chemotherapy.…”
Section: Correlation Between Human Epidermal Growth Factor Receptor 2mentioning
confidence: 81%
“…Both univariate and multivariate analyses suggested distinctly longer survival in the 261 patients with continued trastuzumab treatment. These results are presented in a separate publication [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence supports the benefits of continuing trastuzumab beyond disease progression in patients with HER2-positive breast cancer 93,94 . The results of these studies suggest that continuing trastuzumab after progressive disease in gastroesophageal cancer is a viable option; however, large prospective studies in patients with gastroesophageal cancer are needed to confirm this approach.…”
Section: Her2-positive Diseasementioning
confidence: 99%